Hubungan Perilaku dengan Kejadian Tuberkulosis Paru di Kabupaten Muna - Arfiyan Sukmadi; La Rangki (STIKes Payung Negeri Pekanbaru, 2021)
Background: The medical record data at the Napabalano Health Center for pulmonary TB in 2016 from January to December was 315 suspected cases, where in 2017 on the January-December period there are 261 cases of pulmonary TB were suspected. Research Purpose: This study aims to analyze the risk factors for TB pulmonary disease in Napabalano District, Muna Regency. Research Method: The research design is the Case Control Study. The study population was all suspected pulmonary TB in Napabalano Subdistrict, Muna Regency, from January to December 2017 totaling 261 cases with the number of sample cases 57 and controls 57 taken with Simple Random Sampling technique. Research Result: Knowledge is a risk factor for pulmonary TB, respondents with less knowledge at risk of suffering the pulmonary TB 4 times compared with respondents with sufficient knowledge. Behavior is a risk factor for the incidence of pulmonary TB, respondents with less behavior are at risk of suffering the pulmonary TB 5 times compared to respondents with sufficient behavior. Conclusions: There is that there are risk factors for knowledge and behavior towards the incidence of pulmonary TB. Suggestions need counseling on prevention behavior of tuberculosis. Keywords: Occurrence of Pulmonary TB, Knowledge and Behavior